An investigation into war metaphors in articles about the Vietnam war from 1954 to 1975 in English and Vietnamese - Đỗ, Thị Kim Chung; Trần Quang Hải, Ph.D. (ĐHĐN., 2014)
Metaphor is a typical and effective rhetoric device, especially conceptual metaphor, is a vital tool of thought and a cognitive device for humans to conceptualize abstract domains. Base on the theories of metaphor, this study makes an investigation into conceptual metaphors used war metaphors in articles about the Vietnam War from 1954 to 1975. Moreover, this study is intended to categorize the Cognitive Metaphors (CMs) of War bases on 400 samples from different articles in English and Vietnamese then analyze and discuss the CMs of War in terms of meaning, structure, mapping. Besides, it also finds out and explains the similarities and differences in the cognitive metaphors used for “war” concept. From the result of thesis, some implications for teaching, learning and translating of conceptual metaphors will be suggested. This also helps Vietnamese learners of English achieve better competence in a cross- cultural communication
Keywords: The English language; metaphors -- metaphors in articles